Contribution of indigenous anti-diabetic flora in Almora district, Uttarakhand, India - Tewari2, Priti Kumari1,2*, G. C. Joshi1, L. M. (Current Botany, 2011)
Uttarakhand is characterized by a rich diversity of ethno-medicinal plants as well as a rich heritage of traditional medicine system. An ethno-botanical survey was conducted to collect information about medicinal plants used for the treatment of diabetes at Almora district. The indigenous knowledge of local traditional plants used for the treatment of diabetes were catalogued based on the collection during the field trips and the information was gathered through interviews conducted with local knowledgeable villagers of selected study areas. Use of ethno-medicine was studied on approx. 100 peoples suffering by this disease. The results showed that the inhabitants use 16 species belonging to 13 families to treat diabetics. They used frequently ethno- medicine for their hypoglycemic activities.